Cognitive Appraisal as a Predictor of Cognitive Emotion Regulation Choice1. (11th November 2015) - Sakakibara, Ryota; Endo, Toshihiko
Abstract: More attention has recently been focused on how a person may choose their emotion regulation strategies depending on the situation. The present research examined how people cognitively appraised a situation that they had actually encountered in their life and how this appraisal affected their subsequent cognitive emotion regulation strategies. Three hundred and twenty‐four participants were instructed to recall the most stressful situation in the last month, and to rate how they cognitively appraised the situation (threat, centrality, controllability, commitment, injustice/unfairness, expectedness, expectancy) and how they cognitively regulated their emotion (self‐blame, blaming others, acceptance, refocus on planning, positive refocusing, rumination, positive reappraisal, putting into perspective, catastrophizing). Multiple regression analysis revealed that even after control for other variables, such as age, sex, personality, the time when the situation occurred and the intensity of negative emotion, all criteria of cognitive appraisal except for expectedness predicted cognitive emotion regulation choice. Implications and limitations of this research are discussed.